The Paradox of the CLT Practice in Indonesia: Challenges and Constraints - shofie; Fahry Rizaldy Putra (Merwinspy Publisher, 2024)
Indonesia has already used the communicative language teaching (CLT) approach for more than two decades, and research from that time reveals its challenges. This paper aims to synthesize past research to address challenges and constraints in CLT implementation and then suggest ways to tackle the mentioned challenges and constraints. The comprehensive framework from Fadilah (2018) was used to identify four broad categories of challenges. This helped us classify challenges by source and then to solve them. The finding of this study by analyzing Indonesian CLT implantation research is that the challenges of CLT can be divided into four frameworks: a) societal classroom constraints include teacher beliefs, teacher beliefs vs students’ preferences, and teachers' workload; b) socioeconomic constraints include class size, grammar-based syllabus, the low of students’ participation, unequal educational recourses c) cultural constraints include, local norms, students anxiety, and embarrassment; d) ideological constraints include English as a foreign language. Further, this paper concludes that these challenges are interconnected and require a systematic approach, with government intervention as a potential first step. This paper offers research-based practical and theoretical recommendations to develop the CLT practice in a specific context.